Increased patterns of Islamic social interaction with E-Learning-based learning methods during the COVID-19 Pandemic: Peningkatan pola interaksi sosial islami dengan metode pembelajaran berbasis E-Learning di masa Pandemi COVID-19 - Mumthaza, Silwana; Anshori, Isa; Istikomah, Istikomah (Halaqa: Islamic Education Journal, 2021)
The spread of Corona in the world in 2019-2020 caused a global pandemic. The COVID 19 pandemic is forcing changes on many fronts. This impact also affects education in a big way. Meanwhile, the school acts as a forum to form intellectualism and values that arise in individuals so that they are able to influence social changes in society continu- ously and massively. The goal is for individuals to be able to survive and adapt in this pandemic.Various educational innovations were made as a step to be able to survive with the interaction of the realm of education. Learning process innovation is an impor- tant strategy in school innovation. The use of ICT is carried out as an effort to improve the business of running education. Elearning is a learning model that can be applied with limited mobility. However elearning is a double-edged knife-like tool. On the one hand, this method has effectiveness that can work during a pandemic. But on the other hand there are social changes that occur as a result of e-learning. This social change changes the transition of knowledge, attitudes, beliefs, skills and other aspects. As a result, social changes in education as a process of teaching and learning will experience social shifts.The social shift that occurs is a form of change in social interaction. The sociological approach to education is used to understand the changes in interaction that arise in e-learning. Limited due to this pandemic, humans must still have to perform their function as social individuals to influence each other. Education as a forum for influence must carry out this interaction through e-learning.Social interaction is one of social activi- ties and integration. Contact and communication will create social interaction so that they are able to carry out a role in their life. This interaction is both associative and dissocia- tive.The identification of social interactions in e-learning learning can provide insight to the teacher in providing important strategies in more meaningful learning so that learning objectives can be achieved. Teachers can also explore the potential of e-learning as an alternative to future education.